2005
DOI: 10.1163/156853905774831837
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of reduced incubation cost on clutch attendance by male and female European starlings

Abstract: SummaryIn biparental birds, the relative contribution of the sexes to parental care can be viewed as a co-operative equilibrium that reflects the relative costs and benefits to each parent. If there are asymmetries in these costs or benefits, then any changes to the cost of care could result in a corresponding adjustment to their relative contribution. Incubation is a parental activity, shared in many species, which is costly both in terms of energy expenditure and time. In this study we manipulated the cost o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
(77 reference statements)
2
3
0
Order By: Relevance
“…In contrast, male nest attendance time was not related to the behaviour of the genetic father, however, it was influenced negatively by humidity, suggesting a more flexible response and compensation to changes in the non-social environment by males than by females during incubation. Our results are in line with previous studies reporting male and female parents to react differently to environmental changes in various bird species (Magrath et al, 2005;Charmantier et al, 2008;Kosztolányi et al, 2009;Vincze et al, 2017;Rohwer and Purcell, 2019;Sharpe et al, 2021;Ton et al, 2021). In zebra finches, a recent study also corroborates our finding suggesting sexually different flexibility and reactions to changing environmental conditions, however, with a sexually contrasting effect of ambient temperature (Ton et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, male nest attendance time was not related to the behaviour of the genetic father, however, it was influenced negatively by humidity, suggesting a more flexible response and compensation to changes in the non-social environment by males than by females during incubation. Our results are in line with previous studies reporting male and female parents to react differently to environmental changes in various bird species (Magrath et al, 2005;Charmantier et al, 2008;Kosztolányi et al, 2009;Vincze et al, 2017;Rohwer and Purcell, 2019;Sharpe et al, 2021;Ton et al, 2021). In zebra finches, a recent study also corroborates our finding suggesting sexually different flexibility and reactions to changing environmental conditions, however, with a sexually contrasting effect of ambient temperature (Ton et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…However, the increase in nest attendance by males may represent compensation for the reduced attentiveness by the female, consistent with results of Magrath et al (2005). The optimal contribution by one parent should depend on the level of investment by their partner, with a reduction in effort by one parent predicted to result in partial compensation by the other.…”
Section: Discussionsupporting
confidence: 76%
“…Our study demonstrated that female Black-necked Cranes shifted priority between self-maintenance and incubation demands depending on various temperature conditions and their parental cooperation. Similarly, Magrath et al (2005) reported that females were more sensitive to the thermal status and demands of the clutch than males.…”
Section: Discussionmentioning
confidence: 97%
“…Differences in attentiveness between male and female Zebra Finches reflect theoretical expectations (Møller & Cuervo 2000) and have been known for a long time (El‐Wailly 1966), but sex variation in behavioural incubation responses to ambient temperature is poorly documented (van Overveld et al . 2005) and its causes are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…1984) and have also identified sex‐dependent differences in attentiveness for European Starlings Sturnus vulgaris (van Overveld et al . 2005). Although available studies are extremely valuable in broadening our understanding of parental and embryonic plastic adjustments to ambient temperature variation, they still provide an incomplete test of these mechanisms.…”
mentioning
confidence: 99%